Demographic Change and Public Libraries – Largeprint and Audio books are not enough! - Düren, Petra (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
Demographic change needs to be considered in public libraries. It’s one of the most important aspects and challenges in libraries in the upcoming years – especially against the background of constantly decreasing budgets. Nowadays several ideas for new services for older people can already be found, such as a media delivery service – library volunteers who bring books and other media to older people – (for example practiced in the public libraries ‘Bücherhallen Hamburg’), links and programmes targeting those aged 50 and older (for example a collection of ‘50+links’ can be found at the homepage of the New York Public Library) or special older adult events, for instance programmes with speakers or films as well as computer classes. In two public libraries in Hamburg and Wedel quantitative research projects took place to find out what older people expect from libraries and what they don’t want or need. It can be seen that questionnaires are a good method to learn more about older users’ needs and wishes concerning their library. For one of the above mentioned surveys not only active users of this public library have been asked to complete the questionnaire but also former users as well as non-users.